What Makes Cities Sustainable? Empirical Evidence From a Brazilian Context - Agostinho, Feni; Pierucci, Pedro; Fonseca, Tamara; Almeida, Cecilia M. V. B.; Giannetti, Biagio F. (Frontiers in Sustainable Cities, 2022)
About 70% of the world's population will live in urban areas by 2050, emphasizing the importance of assessment tools to guide decisions towards more sustainable cities. The ‘Mandala ODS’ is an alternative tool promoted by the Brazilian government to quantify the sustainability of cities based on the UN SDGs. Although diagnoses are important steps for governance, the behavioral profile of decision makers also appears as a key aspect. This work aims to assess the potential association evidence among biophysical, socioeconomic and cultural variables with city sustainability as measured by the ‘Mandala ODS’. A sample of 130 Brazilian cities is considered as a sample, and the Pearson's chi-square indicator is calculated for association analysis. Results show that Brazilian cities located in the South/Southeast/Midwest regions, with HDI higher than 0.75, incidence of poverty lower than 40%, territorial area lower than 3,000 km2, and GDP/capita higher than 25,000 R/person.yr, have significant statistical association that leads them to higher levels of sustainability than other cities without these characteristics. Population density, academic background of mayors, their political ideology and gender showed no association with city sustainability. These findings highlight the fundamental role of governance focused on local characteristics instead of standardized and larger scale based public policies that would hardly bring the same benefits for all cities with different socioeconomic and cultural characteristics. Although additional efforts are still needed to achieve a more comprehensive picture, this work contributes to the discussions about what leads some cities to achieve higher degrees of sustainability than others.